Polymer microfluidic devices : sealing and lamination of topas microfluidic devices by thermal bonding - Li, Aaron Shi Wei. (2010)
This project aims to evaluate and optimize the thermal bonding parameters in order to fabricate TOPAS Cyclic Olefin Copolymer (COC) micro-channeled devices with good replication accuracy that can withstand the pressures subjected by fluid flow during applications.